Mewujudkan Kampung Pulo sebagai Eco-Compact City - PRASETYO, ADITYAS; SYAKUR, DWI ABDUL; PURWANTO, EKO BUDI; TESTAROSSA, FERRARI ALIFA; AL-IRSYAD, MUHAMMAD; RADNAWATI, DAISY; SYAHADAT, RAY MARCH; PUTRA, PRIAMBUDI TRIE (Jurnal Arsitektur Lansekap; Vol.3, No.2, Oktober 2017DO - 10.24843/JAL.2017.v03.i02.p06, 2017)
An urban village (kampong) is an important element in a city to support various activities of a city including commerce and government. Thus the urban village landscape planning is also important because can rehabilitate the urban village from their complex problem like density, public open space, environmental quality, and social problem. This is what underlies this research conducted in Kampung Pulo, East Jakarta. The aims of this study were to plan Kampung Pulo as a village in urban area with the concept of eco-compact city and to overcome various problems in the area. The research methods were literature study, observation, interview, and graphic illustration. Kampung Pulo was planned with eco-compact city model. The model described by land use with building compaction, access efficiency, and optimize the ecological value element.